Design of new super-high birefringent isothiocyanato bistolanes – synthesis and properties. Issue 9 (15th July 2017) - Herman, Jakub; Kula, Przemysław
ABSTRACT: We report the synthesis of new laterally ethyl-substituted high birefringent phenylethynyltolane liquid crystals with alkylsulphanyl chain and isothiocyanate terminal group. The thermal and optical properties such as birefringence are measured and discussed based on their molecular structures. The compounds exhibit birefringence (Δn) in the range of 0.63– 0.75 and are expected to be excellent components of high birefringent nematic mixtures for various applications. Graphical Abstract: